Cisco Routers for the Small Business - Neumann, Jason C. (Apress, 2012)
“The creation of this book, like many things in life, was a complete accident.” This book is intended for the average network administrators or IT professionals who manage small networks and are currently using, or want to use Cisco IOS-based routers in their networks. After all, why should Cisco routers be reserved for elite Cisco gurus when all you need to know are a few simple concepts and commands? This book is about a Cisco CLI for the regular guy or gal. After reading this book, you’ll no longer have to use cheap consumer-grade routers on your small business network. You, too, can have all the reliability and advanced functionality that the Cisco IOS offers. In my experience, the best way to learn this material is through hands-on experience. The more the better! Therefore, you may want to have a spare Cisco router to work with. You can use the book without one, but it really helps to have an actual router on hand to work through the material. The Cisco 831 and 851 routers will be used throughout my examples. If you don’t have a router, you can easily find an older 800 series router on eBay or some other used computer site. In secondary markets like eBay, a Cisco 831 or SOHO91 series router is inexpensive, easy to come by, and will work well with the material. Keep in mind that you will need a router with at least 64 MB of memory to configure DSL using PPPoE. Also, I assume that the router has an IOS version of 12.4 or greater.